Precise Populations’ Description in Dairy Ecosystems Using Digital Droplet PCR: The Case of L. lactis Group in Starters - Caillaud, Marie-Aurore; Abeilhou, Martine; Gonzalez, Ignacio; Audonnet, Marjorie; Gaucheron, Frédéric; Cocaign-Bousquet, Muriel; Tormo, Hélène; Daveran-Mingot, Marie-Line (Frontiers in Microbiology, 2020)
Lactococcus lactis subspecies lactis and cremoris play a major role in dairy fermentations. Usually present in starter cultures, the two subspecies enable efficient acidification and improve the organoleptic qualities of the final product. Biovar diacetylactis strains produce diacetyl and acetoin, aromas from the citrate metabolization. As these populations have distinct genomic and phenotypic characteristics, the proportions of each other will affect the final product. Today, there is no quantitative test able to distinguish between the two subspecies and the biovar in dairy ecosystems. In this study, we developed a specific, reliable, and accurate strategy to quantify these populations using, species-, subspecies- and diacetylactis-specific fluorescent probes in digital droplet PCR assays (ddPCR). Subspecies were distinguished based on three single nucleotide polymorphisms in the glutamate decarboxylase gadB gene, and the citD gene involved in citrate metabolism was used to target the biovar. Used in duplex or singleplex, these probes made it possible to measure the proportion of each subspecies and the biovar among the L. lactis population. At 59 °C, each probe showed target specificity and responded negatively to the non-target species usually found in dairy environments. Depending on the probe, limit of detection values in milk matrix ranged from 3.6 x 103 to 1.8 x 104 copies/ml. The test was applied to quantify L. lactis sub-populations during milk fermentation with a commercial starter. The effect of temperature and pH on the balance of the different populations was pointed out. At the initial state, lactis and cremoris subspecies represent respectively 75% and 28% of the total L. lactis population and biovar diacetylactis strains represent 21% of the lactis subspecies strains. These ratios varied as a function of temperature (22 °C or 35 °C) and acidity (pH4.5 or 4.3) with cremoris subspecies promoted at 22 °C and pH4.5 compared to at 35 °C with the same pH. The biovar diacetylactis strains were less sensitive to acid stress at 35 °C. This methodology proved to be useful for quantifying lactis and cremoris subspecies and biovar diacetylactis and could complete 16S metagenomics studies for the deeply description of L. lactis sub-populations in complex ecosystems.